ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA UNTUK BERKARIR DI SEKTOR KEUANGAN SYARI’AH - FEBRINA, RIA; SARI, SARI (JURNAL AKUNTANSI DAN KEUANGAN, 2025)
The Islamic finance sector in Indonesia has continued to grow and has demonstrated significant development in recent years. This growth has created numerous opportunities within society, one of which is career opportunities. This study aims to identify the factors that influence students’ interest in pursuing a career in the Islamic finance sector using a quantitative approach. The method employed in this research is a survey conducted through an online questionnaire distributed via Google Forms. The sample consists of sixth- and eighth-semester students majoring in Islamic Economics and Islamic Banking in the cities of Duri and Tembilahan. The results indicate that understanding of Islamic finance, religiosity, career perception, and financial expectations have both partial and simultaneous effects on students' interest in pursuing a career in the Islamic finance sector. This study contributes to the theoretical discourse on career interest in the Islamic finance sector by integrating key influencing factors such as knowledge of Islamic finance, religiosity, perception, and financial expectations.